Combined effects of ocean acidification and low temperature on two range expanding hermatypic corals: Acropora solitaryenis and Porites heronensis - Lugué, Klervi (2021)
A recent poleward shift of hermatypic corals’ distribution has been reported and was attributed to the increase in sea temperature since the pre-industrial revolution. Ocean acidification and predicted increasing variability of sea surface temperatures, may together limit this shift in the future. The objective of this study was to investigate whether a tipping point exists in the physiological and metabolic responses of Acropora solitaryensis and Porites heronensis, to CO2, under average winter temperature and under cold event temperature (cold stress; -4°C decrease).We studied the effects of increased partial pressures of CO2 (pCO2) from 294 ppm to 5018 ppm, on a set of metabolic parameters. The light and dark calcification, skeletal growth rate, chlorophyll and protein concentrations decreased linearly as a function of increasing partial pCO2 in A. solitaryensis. In comparison only the dark calcification and skeletal growth rate decreased linearly as a function of increasing partial pCO2 in P. heronensis. For both species, the cold stress acted as an additional stress to the pCO2 exposure, except for the respiration in P. heronensis. No physiological tipping point has been identified, beyond which these coral species were no longer capable of carrying out the functions necessary to their survival. The lack of a clear tipping point, as well as the emergence of potential ‘ecological winners’, here P. heronensis, in the face of decreasing pH and cold temperature stress, indicate that in the coming decades the species composition of coral reefs is likely to slowly change, to a new composition in which surviving in marginal high latitudes are those that show the required potential for adaptation. Our study highlights the substantial advantages of the regression method to predict the impacts of ocean acidification. Resolving high resolution relationships between metabolism and pCO2 could greatly improve the accuracy of models describing the effects of future ocean acidification on calcifying organisms and marine ecosystems.